What happens in the long term: Uptake of cancer surveillance and prevention strategies among at‐risk relatives with pathogenic variants detected via cascade testing. Issue 24 (27th October 2022) - Frey, Melissa K.; Ahsan, Muhammad Danyal; Badiner, Nora; Lin, Jenny; Narayan, Priyanka; Nitecki, Roni; Rauh‐Hain, Jose Alejandro; Moss, Haley; Fowlkes, Rana Khan; Thomas, Charlene; Bergeron, Hannah; Christos, Paul; et al.
Abstract: Background: Cascade genetic testing for hereditary cancer syndromes offers affected relatives the opportunity to pursue cancer screening and risk‐reducing surgery and thus reduces morbidity and mortality. The purpose of this study was to measure the long‐term utilization of targeted cancer prevention and quality of life among at‐risk relatives offered clinician‐facilitated cascade genetic testing. Methods: In a pilot study, at‐risk relatives of patients with a hereditary cancer syndrome were contacted directly by the clinical team and offered telephone genetic counseling and genetic testing via an at‐home, mailed saliva kit. Two‐year follow‐up results evaluating the use of targeted cancer prevention strategies and the quality of life for enrolled relatives were reported. Quality‐of‐life was measured with validated surveys, and scores were compared to the time of initial contact by the Wilcoxon signed‐rank test. Results: Ninety‐five at‐risk relatives were enrolled in the initial pilot study, and 72 (76%) participated in the 2‐year follow‐up; 57 of these (79%) had completed genetic testing. Twenty‐five of those 57 relatives (44%) were found to harbor an inherited pathogenic variant. Guideline‐based cancer surveillance was recommended to 18 relatives; 13 (72%) completed at least one recommended screening, and six (33%) completed all recommended screenings. Risk‐reducing surgery was recommended to 10 relatives; four (40%) completed a total of eight procedures. Quality‐of‐life surveys demonstrated low levels of anxiety, depression, distress, and uncertainty. Conclusions: The 2‐year follow‐up of the original pilot study revealed that clinician‐facilitated cascade testing resulted in genetically targeted cancer screening and prevention with preserved quality of life. These results, to be confirmed by larger randomized controlled trials, suggest that medical systems should consider supporting clinician‐facilitated cascade testing programs. Abstract : Cascade testing for cancer syndromes facilitated by the medical team resulted in identification of relatives with pathogenic variants and use of genetically targeted cancer prevention with preserved quality‐of‐life.